Analysis of an Abnormal Faults of UHV DC Low-end YD-A Phase Converter Oil Chromatography. Issue 1 (1st April 2022) - Zhou, Xiu; Ma, Bo; Liu, Weifeng; Tian, Tian; Luo, Yan; Ma, Yunlong; Wang, Hehu
Abstract: The article introduces an abnormal malfunction of YD-A converter oil chromatogram at the low end of UHVDC converter station, through oil chromatography data, ultrasonic positioning, on-site feeding, returning to plant disassembly and simulation calculation, which confirmed that the breakage of the isopotential of the converter electrostatic plate is the cause of the abnormal oil chromatogram and put forward corresponding suggestions and measures.